Expected and realized response in various traits of broiler dam and sire lines - KUMAR, SHIVE; SINGH, R P (The Indian Journal of Animal Sciences, 2011)
A study was conducted on 7672 cockerel and pullet birds of dam line and 3223 cockerel and pullet birds of sire line to know the expected and realized response in various traits of broiler dam and sire lines. The Age at first egg was expected to decrease by–0.20 days and the realized response was found to be similar–0.19 days. The egg number was expected to increase 15.29 eggs and the realized was found to be 11.0 eggs over four generation of selection. The present results pointed out that egg number was improved with negligible decline in egg weight. In most of the broiler traits discrepancies between expected and realized responses were observed in all generations. The possible reason for the discrepancies may be that natural selection might have played its role. Simultaneous selection for several antagonistic traits could minimize selection progress. In over all generation the similar response were observed between expected and realized response for reproductive traits viz. age at first egg and egg number. It means we can judge the egg number and age at first egg through expected response in further generation of commercial broiler dam line.